Incorporating privacy in the design of cloud-based systems: a conceptual meta-model. (13th November 2017) - Kalloniatis, Christos
Abstract : Purpose: The purpose of this paper is to extend PriS (privacy safeguard), a privacy requirements engineering method for eliciting and modelling privacy requirements during system design, with the addition of privacy-aware cloud-based concepts to assist analysts to reason and model about privacy in cloud environments. Design/methodology/approach: An analysis of previous findings on the file of cloud privacy based on previous work has been conducted and a set of privacy-related concepts that need to be considered during privacy analysis for cloud-based systems have been revealed. These concepts were used for extending the conceptual model of PriS. Findings: The main finding of the paper is the design of a new, novel conceptual model that assists analysts and designers in reasoning about privacy in cloud environments. A new template using the JSON (Javascript notation object) format has been introduced for better expressing the privacy requirements along with the related concepts presented through the conceptual model, thus letting the developers to better understand the findings during the design stage and better guide them to the implementation of the respective solution. Research limitations/implications: The design of a cloud-based process that will guide analysts in detail for eliciting and modelling the identified privacy-related requirements is the limitation and in parallel the next step of the specific work presented here. Practical implications: The conceptual model has been applied on a real case scenario regarding its efficiency on capturing and mapping all necessary concepts for assisting analysts proceed with the design of the privacy-aware system. The results were positive, all concepts were easy to use and totally understandable from the design team and the stakeholders and the use of the JSON template received very positive comments, especially from the developer's team. Originality/value: The paper presents a novel conceptual model for reasoning about privacy requirements in the cloud. The applicability of the proposed model has also been tested on a real case study.